2012
DOI: 10.1309/ajcp4inkz6lyaqxw
|View full text |Cite
|
Sign up to set email alerts
|

Extended Use of Serum Free Light Chain as a Biomarker in Lymphoproliferative Disorders

Abstract: Serum free light chain (sFLC) assays were shown to improve detection, management, and prognostication in plasma cell disorders. Recently, sFLC assays improved detection of M proteins when combined with standard methods of protein electrophoresis/immunofixation in patients with non-Hodgkin lymphoma/chronic lymphocytic leukemia (NHL/CLL). Incidence of abnormal sFLC ratio (sFLCr) varied from 0% to 36% and 29.7% to 59% in NHL and CLL, respectively. Increased sFLC levels or abnormal sFLCr predict shorter overall su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…1 Serum assays offer many advantages over the traditional, electrophoretic, urine FLC assays [2][3][4] and have been used widely as an aid for the diagnosis and management of myeloma patients. The International Myeloma Working Group (IMWG) guidelines currently recommend the use of serum FLC (sFLC) assays in diagnostic screening panels and as a "biomarker of malignancy" (involved-to-uninvolved sFLC ratio $100) defining the presence of multiple myeloma (MM) in the absence of other indications.…”
Section: Introductionmentioning
confidence: 99%
“…1 Serum assays offer many advantages over the traditional, electrophoretic, urine FLC assays [2][3][4] and have been used widely as an aid for the diagnosis and management of myeloma patients. The International Myeloma Working Group (IMWG) guidelines currently recommend the use of serum FLC (sFLC) assays in diagnostic screening panels and as a "biomarker of malignancy" (involved-to-uninvolved sFLC ratio $100) defining the presence of multiple myeloma (MM) in the absence of other indications.…”
Section: Introductionmentioning
confidence: 99%
“…21 Determination of the serum levels of kappa and lambda FLC, including the FLC ratio, is a valuable immunological tool for detecting the presence of polyclonal activation and monoclonal dyscrasias of B-lymphocytes and plasma cells. 10,12,22 Although chronic HCV infection has been associated with Bmalignancy, only two studies, both performed with French patients, investigated these biomarkers in cases of chronic hepatitis C. They demonstrated an increase of kappa FLC serum levels in patients with mixed cryoglobulinemia, observing an abnormal FLC ratio in patients with MC vasculitis and B-NHL, with a significant correlation between elevated FLC ratios and cryoglobulin level and severe HCV-related B-NHL. 14,15 In contrast, FLC was shown to be a potential sensitive marker of polyclonal B-cell activation in a cohort of HIVinfected patients, who experienced increased risk of NHL.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this sensitive immunoassay is able to detect very low concentrations of FLC (3-4 mg/L) and is an effective substitute for immunofixation electrophoresis (IFE), which has an analytical sensitivity of only 100-150 mg/L of FLC, for use in the diagnosis of B-and plasma cell dyscrasias. 12,13 Patients who are chronically infected with HCV can present an increased level of FLC and a significant alteration in their FLC ratio, which has been associated with both MC and B-NHL. 14,15 Although we have shown that Brazilian patients with chronic HCV infection present a high prevalence of cryoglobulinemia, no studies have been conducted to investigate markers of B-cell malignancies in these subjects.…”
Section: Introductionmentioning
confidence: 99%
“…While aberrant (unstable) proteins are usually eliminated before they can leave their parent cell [10][11][12][13], under certain circumstances -such as mass synthesis of light chains associated with multiple myeloma -they can be detected in circulation ( Fig. 3.1) [14][15][16][17][18][19].…”
Section: Natural Susceptibility Of Proteins To Bind Congo Redmentioning
confidence: 99%